Investigating The Use of SimDif Website-Based Media in English Language Teaching : (A Descriptive Qualitative Study at SMK Pancasila 3 Baturetno) - Novika Ayu Ardhianti; Hersulastuti; Endang Eko Djati (Yayasan pendidikan dzurriyatul Quran, 2026)
The integration of interactive web-based learning media has become increasingly important in English Language Teaching (ELT), particularly in vocational education where learning relevance and practical communication skills are essential. This study aims to explore the implementation of the SimDif website as an interactive learning medium in vocational English classrooms, focusing on its instructional process, challenges, influence on students’ motivation and engagement, as well as its perceived benefits and limitations. This research employed a qualitative descriptive design conducted at SMK Pancasila 3 Baturetno. The participants consisted of a teacher collaborator and Grade XI Technical Machining students. Data were collected through classroom observations, student interviews, and a teacher collaborator interview. Classroom field notes were used to capture learning activities, interactions, and student responses during the implementation of SimDif. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. The findings reveal that SimDif was implemented through structured stages, including platform introduction, analysis of model texts, guided website creation, and student presentations. Despite challenges related to internet connectivity, time management, and students’ initial digital skills, the use of SimDif positively influenced students’ motivation and engagement. Students demonstrated increased participation, confidence, collaboration, and autonomy in learning English, particularly when completing vocationally relevant tasks. Furthermore, SimDif facilitated authentic language use by connecting English learning with students’ vocational contexts, although its effectiveness depended on teachers’ pedagogical and technological readiness. In conclusion, SimDif functions as a meaningful interactive web-based learning medium that supports student-centered, motivating, and contextually relevant English learning in vocational schools. This study suggests that teacher guidance, task design, and infrastructure support are crucial to maximize the pedagogical potential of website-based learning media in ELT.